A 26–47.9 GHz ultrawideband CMOS dual injection‐locked frequency divider. Issue 9 (September 2014) - Liu, Faen; Wang, Zhigong; Li, Zhiqun; Li, Qin; Yang, Geliang
ABSTRACT A 26–47.9 GHz ultrawideband CMOS dual injection‐locked frequency divider (dual‐ILFD) with high input impedance is demonstrated. As the differential input signal is injected into the gate of the PMOS tail transistor and NMOS switch transistor, the proposed divider has high input impedance and can be driven easily by the preceding driving circuits. Meanwhile, the locking range of the proposed divider is extended significantly by fully utilizing the dual‐injection technique. The proposed dual‐ILFD is fabricated in a standard 90‐nm CMOS process and on‐wafer measurements are performed. The measurements show that the free‐running frequency of the divider is 19.11 GHz. At an incident power of 0 dBm, a total locking range from 26 to 47.9 GHz is achieved. The power consumption is 2.88 mW at a supply voltage of 1.2 V. The total chip size is 0.62 × 0.42 mm2. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:2126–2129, 2014